PEMBUATAN DAN INSTALASI JAM WAKTU SHOLAT DAN SISTEM PENJERNIHAN AIR DI PONDOK PESANTREN HIDAYATUL MUSLIMIN 1 - Agus Riyanto; Hasan Hasan; Mohd. Ilyas Hadikusuma; Medi Yuwono Tharam; Satriyo Satriyo; M. Ridwan Sufandi; Eko Mardianto; Yohanes C.H Yuwono; Nanda Rusyda Saufa; Wiwit Indah Rahayu (Politeknik 'Aisyiyah Pontianak, 2024)
The community service program is one of the knowledges implementation activities to be useful in the community. This program is also can be used as socializing the D-IV Study Program in Electronics System Engineering Technology (TRSE), Pontianak State Polytechnic to the students in high school. The location of activities was Islamic Boarding School of Hidayatul Muslimin 1 Islamic Boarding School, Kubu Raya Regency. This school including orphanage, Madrasah Tsanawiyah (Junior High School), and Ulya Equivalency Education (High School Level). This program was carried out using service learning method by providing practical technology implementation and brief training on the use of the technology provided. The activities include were build-up dan installations of Prayer Time Clocks (JWS) and water purification systems for wudhu at the Sulaiman Mosque (for female students). In addition to the installation, the school was also given socialization about the installation and use of JWS and the importance of clean water in student’s daily activities. The implementation of this activity, it is hoped that the TRSE Study Program of Pontianak State Polytechnic can be widely recognized and bring more benefits to the community.